2015
DOI: 10.1177/230949901502300105
|View full text |Cite
|
Sign up to set email alerts
|

Combined Volar and Dorsal Plating for Complex Comminuted Distal Radial Fractures

Abstract: Combined volar and dorsal plating enables early mobilisation and good outcome for certain complex comminuted distal radial fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Several reports show that the VLP is related to tendon related complications, even necessitating plate removal and resurgery [ 8 ].However, we did not experience such complications in our patient group, possibly as a result of appropriate patient selection, careful soft tissue dissection and precise screw lengths. Farhan et al reported in their series of patients with AO23C3 distal radius fractures that 16% of the patients required plate removal [ 23 ]. In our series, we had only one patient with an AO23C3 type fracture, and we treated the patient using EF, and the patient had an event-free follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that the VLP is related to tendon related complications, even necessitating plate removal and resurgery [ 8 ].However, we did not experience such complications in our patient group, possibly as a result of appropriate patient selection, careful soft tissue dissection and precise screw lengths. Farhan et al reported in their series of patients with AO23C3 distal radius fractures that 16% of the patients required plate removal [ 23 ]. In our series, we had only one patient with an AO23C3 type fracture, and we treated the patient using EF, and the patient had an event-free follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Farhan et al [21] reviewing data of 24 patients with severe comminuted fracture of distal radius treated by double plating, reported complications such as tendon rupture, carpal tunnel syndrome, infection and non-union, in addition to the early removal of dorsal plate among four patients. Besides, they concluded that double plating has the advantages of early motion and good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Due to less soft tissue on the dorsal side of the wrist, there may be higher likelihood of tendon irritation and need for hardware removal, although new lower profile plates may help mitigate this problem. Farhan et al, in their retrospective series of 24 patients with AO C3 distal radius fractures treated with combined volar and dorsal plating, 4 patients required plate removal [6].…”
Section: Dorsal Monoblock Platingmentioning
confidence: 99%
“…There is a high rate of concomitant scapholunate interosseous ligament injury with high energy distal radius fractures [6]. Diagnosis relies on either radiographic SL distance and SL angle or intraoperative fluoroscopic or arthroscopic assessment.…”
Section: Scapholunate Ligament Injurymentioning
confidence: 99%